Investigation of Knowledge, Attitude and Practice of Pregnant Women regarding Nutrition during Pregnancy in Yazd City - Seyed Saeed Mazloomy Mahmoodabad; Marziye Taftiyan; Hassan Mozaffari- Khosravi; Nooshin Yoshany; Masoomeh Goodarzi-Khoigani (Shahid Sadoughi University of Medical Sciences, 2018)
Introduction: Pregnancy is one of the most important stages in maternal and fetal life, in which mother's need for energy and food during this period increases due to physiological changes. As a result, mother's nutritional status has a significant impact on her health, her fetus, pregnancy outcomes and ultimately the community. Studies have shown that nutritional knowledge and attitudes affect nutrition effectively. Therefore, this study was conducted with the aim of determining the knowledge, attitude and practice (KAP) of pregnant women regarding nutrition during pregnancy in Yazd. Methods: This cross-sectional descriptive study was performed on 120 pregnant women in Yazd health center during summer 1396. The questionnaires in this study were researcher-made including demographic variables, knowledge, attitude and practice of pregnant women. Finally, data were analyzed using descriptive statistics and coloration in SPSS version 18. Results: The results showed that knowledge in 33.3% of pregnant women was poor, 64.2% moderate and 2.5% good. The attitude of most people (98.2%) was positive towards proper nutrition during pregnancy. The performance of 70% of people was moderate about nutrition during pregnancy. Conclusion: According to the results of this study, the knowledge and practice of most people in the field of nutrition during pregnancy was in the medium range. Furthermore, the attitude of most people was positive towards nutrition. Therefore, educational programs to improve the knowledge and practice of pregnant women should be implemented by pregnant care providers.